The Carmelite Order and Greek Orthodox Monasticism: a Study in Retrospective Unity - Jotischky, Andrew (Studies in church history, 1996)
On his embassy from Constantinople to the papal curia in 1339, the Greek Orthodox envoy Barlaam confided to Benedict XII his pessimistic belief that genuine union between the Churches was rendered impossible less by theological difference than by the shared history of relations between eastern and western Christendom: It is not so much the difference in doctrine that alienates the hearts of the Greeks from you as the hatred against the Latins that has entered their souls because of the great number of evils they have suffered at the hands of the Latins at different times, and which they still suffer every day. Unless this hatred is dispelled, union can never be achieved.